PARADIGMA IMPLEMENTASI KONSEP REVOLUSI MENTAL - Buyung Syukron (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
Mental revolution meant as a change of mindset (mindset) in the life of the nation. Mental revolution is not enough to rely on good intentions, but must take into account structural changes in interaction community. In the realm of mental revolution, Islamic education should consider the structure of the definition, domination, and legitimacy. Third it is customize the mindset of Islamic education principals, Islamic education system, and the structure of the institution of Islam itself. Orientation changes as the impact of the implementation of a mental revolution must be presented with a form in the form of improved educational services for the welfare of the community. Islamic educational institutions expect being able to parse about injustice, arbitrariness and human made in respect of, feel, think, and act in a more rational and sensible.